"... allerlei für die Nationalbibliothek zu ergattern..." Eine österreichische Institution in der NS-Zeit - Hall, Murray G. (2006)
When Austria was annexed by Hitler Germany in March 1938, the National Library in Vienna was not only the biggest scientific library in the country, it was now the third largest in the German Reich. Its status among and influence on the scholarly libraries in the Reich was considerably enhanced by one person during the Nazi period, namely the newly-appointed director-general Dr. Paul Heigl, a fervent National socialist, Acquisitions by the Library during the years 1938 to 1945 are a key focal point of this history, and Heigl played both an active and significant role in the process of book looting in the interest of the National Library. The Library may well have regarded itself in the inter-war years as being "apolitical" - and house historians have tended to reinforce this image - but this does not stand up to closer scrutiny even during the political period of the "Corporate State" und Dollfuss and Schuschnigg, let alone during the time of national socialist rule in Austria. The study breaks with the previos taboos and presents the essentially political role of the Library both before and after March 1938 by investigating its involvement in the crimes of the Nazi regime. But the study does not only concentrate on acquisitions made through improper means, it also attempts to capture some of the atmosphere of a major library under the NS-regime and in war-time. The examination also sees itself as a contribution to the hitherto neglected history of libraries in Austria in the Nazi period in general and of church and official libraries in particular. It might be noted that Paul Heigl was not only in charge of scholary libraries in south-eastern Europe following the German invasion of Yugoslavia in April 1941, he was also a library consultant for local Nazi officials and had considerable sway in forging library policy. Our study discusses a number of chapters in the Library ´s history during the Nazi period which have so far been absent from official histories, primarily those which implicate the Library and point to the vast and varied acquisitions. The main chapter focusses on the development and acquisitions of the Library´s many collections from 1938 o 1945, chiefly on the basis of library records and files, and attempts to describe not only the looting, but also fate of stolen books, libraries and collections immediately after World War Two and on up to the present day. And, as the case may be, their subsequent restitution over the past few years as a consequence of the Art Restitution Law of 1998. Name and subject indices are intended to make the information in thistory more easily accessible.